Gods, Religion and Its Criticism in the Greek Aesopic Fables - Michał Wojciechowski (Studia Warmińskie, 2023)
About a hundred Greek fables from the Aesopic tradition contain direct or allegorical references to religion. These references were not sufficiently studied. As a whole, they represent an anonymous, popular approach to religion from the Hellenistic period, with some sources in the earlier times. They have some importance for the history of Greek religion. These fables may be divided into two groups. The first group presents gods and mythology, with the dominant role of Zeus, near to henotheism; other gods are not really important. However, Prometheus is sometimes presented as the maker. The second group contains criticisms of religion, idolatry and misguided prayer (with Hermes as the butt of jokes).